A new method to estimate thermal conductivity of polymer composite using characteristics of fillers. Issue 3 (22nd November 2012) - Park, Hui Joon; Kim, Tae Ann; Kim, Raehyun; Kim, Junkyung; Park, Min
Abstract In this work, a new method to estimate the thermal conductivity of polymer composite was suggested. For this purpose, polymer composites composed of high‐density polyethylene (HDPE) and boron nitride (BN) were prepared by twin‐screw extruder melt‐mixing, followed by compression molding technique, and their microstructure was investigated by material simulation. Consequently, the Cf parameter of Agari and Uno equation, which represents an ease in forming conductive chains, was quantified by "Structure factor (related with conductive pathway)" and "Interfacial factors (related with thermal resistance)", ultimately helping us evaluate the thermal conductivity of arbitrary composite system. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013